The coefficients of variable x in equation 6x - 3y = -4 is 6 and in equation -4x - y = 5 is -4.
So coefficients of x in both the equation can be made equal to each other by multiplication of 6 by 2 and multiplication of -4 by 3.
So after multiplication by 2 to equation 6x - 3y = -4, coefficients of variable x is 12, and after multiplication by 3 to equation -4x - y = 5, coefficients of variable x is -12 which cancels out each other on addition.
So correct answer is A option muiltply A by 2 and B by 3